Controlling Ourselves: Emotional Intelligence, the Marshmallow Test, and the Inheritance of Race - Staub, Michael E. (American Studies, 2016)
What does the immensely successful and culturally influential “marshmallow test,” developed by psychologist Walter Mischel to measure a child’s ability to demonstrate self-control and resist immediate temptation, have to do with the history of race in the United States? Already in the 1960s, Mischel’s experiments on the delay of gratification had been cited in the Moynihan Report as well as other public policy pronouncements that sought to analyze why many African Americans remained mired in poverty. Yet the story of race and self-control has a far longer history that dates back at least to the New Deal era when social scientists linked self-denial to middle-class and white neuroses. By the 1950s, however, self-control assumed a prominent (if contradictory) place in criminology and studies in juvenile delinquency. Although this was a legacy Mischel initially critiqued, his gratification delay experiments came by the 1970s and 1980s directly to inform more overtly right-wing (and racialized) social theories that openly linked low delay with low IQ and criminal behavior. By the 1990s, with the rise of positive psychology and a concept of emotional intelligence (EI) that heralded self-control as a “master aptitude,” the ways in which self-control had been inseparable from the histories of race and class were erased almost entirely. Reconstructing this ambiguous history offers insights not only into a forgotten postwar American story, but also what has been at stake in debates over educational reforms in our present.